STATE AUDIT OF ENVIRONMENTAL PROTECTION - E. V. Nikiforova; B. A. Alibekova; A. N. Rakaeva; Zh. Zh.Otegulova (Scientific Journal of Pedagogy and Economics, 2019)
The article considers the introduction of the state audit of environmental protection in the republic in connection with the reform of the financial control bodies in accordance with international best practice. The purpose of the article is to reveal the essence of the state audit of environmental protection. As a result of the study, the authors found that at present there is no single definition of an audit of environmental protection at both the international and national levels. On the basis of a comparative analysis of scientific and special literature, it has been revealed that three approaches have emerged in the formation of the concept of environmental audit. The features of the audit of environmental protection conducted by the state audit bodies are disclosed and, taking into account the results of a comparative analysis of the literature, its author’s definition is given. To ensure efficiency, economy, productivity and effectiveness indicators of the use of natural resources and budget funds it has been identified the need for adoption of a regulatory document governing the conduct of an audit of environmental protection by state auditors and the use of its results.